Respuesta :

Gah06

Answer:

D. 1

Step-by-step explanation:

You are given the values of x that correspond to g(x).

Then you are given f(g(1)), the function of f, the function of g(x) at 1.

When x is 1, g(x) is 0.

f(x) is 3 times the square root of x plus 1.

Since x is now 0, three times the square root of 0 is still zero. The one remains.

   Given function → [tex]f(x)=3\sqrt{x} +1[/tex]

In the picture attached, for every value of 'x', value of function 'g' has been given.

For x = 1, g(1) = 0

Now substitute the value of g(1) in function 'f',

[tex]f(g(1))=f(0)[/tex]

Since, [tex]f(x)=3\sqrt{x} +1[/tex]

Therefore, [tex]f(0)=3\sqrt{0}+1[/tex]

                         [tex]=1[/tex]

    Hence, Option D will be the correct option.

Learn more,

https://brainly.com/question/1757488

ACCESS MORE